‘Peregrinatio’ and ‘Peregrini’ in Augustine's ‘City of God’ - Claussen, M. A. (Traditio, 1991)
To most people inclined, in the late twentieth century, to think in such terms, the idea of pilgrimage as a metaphor for the Christian life seems natural and almost perfect — natural and perfect to the extent that it is often assumed to have been the metaphor for such a life from the beginnings of the religion. This is not the case. Although the image of pilgrimage — peregrinatio — can be found occasionally in earlier fathers, it did not receive a full theological exposition until Augustine's City of God in the early fifth century. There, peregrinatio is linked directly to the theme of the two cities, the essential and basic conceit of the book. Even in the very first sentence, Augustine says that he will seek to defend